1994
DOI: 10.1161/01.str.25.11.2187
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler detection of vertebrobasilar vasospasm following subarachnoid hemorrhage.

Abstract: Background and Purpose Transcranial Doppler sonography is of established value in the detection and monitoring of middle cerebral artery vasospasm. Little information exists on the utility of transcranial Doppler for detection of posterior circulation vasospasm.Methods Cerebral angiography and conventional handheld transcranial Doppler sonography were compared to determine sensitivity and specificity of transcranial Doppler for detection of vertebral and basilar artery vasospasm.Results Of 59 consecutive subar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(81 citation statements)
references
References 62 publications
(12 reference statements)
2
77
0
2
Order By: Relevance
“…Numerous studies showed the effectiveness of TCD in diagnosing cerebral vasospasm, both in the anterior and posterior circulation after SAH, allowing early planning of interventions, including angioplasty and nicardipine infusions [60,61]. A detailed review of this application of TCD and the role of CTA in SAH is largely outside the scope of our article, which focuses mostly on ischemic stroke.…”
Section: Transcranial Doppler and Transcranial Duplexmentioning
confidence: 99%
“…Numerous studies showed the effectiveness of TCD in diagnosing cerebral vasospasm, both in the anterior and posterior circulation after SAH, allowing early planning of interventions, including angioplasty and nicardipine infusions [60,61]. A detailed review of this application of TCD and the role of CTA in SAH is largely outside the scope of our article, which focuses mostly on ischemic stroke.…”
Section: Transcranial Doppler and Transcranial Duplexmentioning
confidence: 99%
“…In a recent meta-analysis, 91 only 5 of 26 evaluable TCD studies [93][94][95][96][97] met at least 7 of 10 criteria for methodologically high-quality studies. In general, data vary by vessel and by diagnostic criteria, disease prevalence, and timing of correlative angiography.…”
Section: R E T I R E D R E T I R E Dmentioning
confidence: 99%
“…The specificity of TCD can be optimized by increasing the flow velocity criteria and sensitivity by the timing of the angiographic correlation for the diagnosis of VSP. 94,95 TCD is useful in monitoring the temporal course of angiographic VSP after sSAH. Although no adequate study has been conducted, TCD is thought to be valuable in the day-to-day evaluation of sSAH patients in VSP and to assess the effect and durability of neuroradiologic interventions.…”
Section: R E T I R E D R E T I R E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…14,17,20) Finally, patients with posterior circulation aneurysms were excluded from this study. However, those patients are not likely to suffer from SVS, 26) so the influence is small in this study.…”
Section: Discussionmentioning
confidence: 92%